'Anarchist technologies': Anarchism, cybernetics and mutual aid in community responses to the COVID-19 crisis. (January 2023) - Swann, Thomas
The COVID-19 pandemic that gripped the world since the end of 2019 has been felt most immediately both as a health crisis and an economic, social and political crisis. Secondary impacts of social distancing and lockdown in many countries have put strains on people's capacities to provide essential food and medicines for themselves and their families. In response, outside of centralised government and voluntary sector frameworks, local mutual aid groups have emerged around the world as a primary site of community resilience. Given mutual aid's strong links to the anarchist political tradition, for example in its identification by Kropotkin as a factor in evolution, this article suggests that these new mutual aid groups can be understood best through the related concept of self-organisation. Tying anarchist approaches to mutual aid and self-organisation together, it is argued that cybernetics and Stafford Beer's Viable System Model (VSM) offer useful tools in helping both academic analysis and on-the-ground practice assess and improve the effectiveness of mutual aid in and beyond the COVID-19 crisis. The article offers a qualitative thematic analysis of anarchist and related texts published during the pandemic that reflect on mutual aid practice. In doing so, it highlights some of the challenges and tensions such self-organised mutual aid practice might face and proposes a participatory research agenda drawing on Beer's VSM.